Upscaling Aboveground Biomass Estimation at Low-land Royal Belum Forest Reserve Using Unmanned Aerial Vehicle Image - Rasib, Abd Wahid; Mohd Ali, Hamzah; Alvin, L.M.S.; Kanniah, K.D.; Idris, Nurul Hawani; Omar, Hamdan; Faidi, Azahari; Dollah, Rozilawati; Anjang Ahmad, Mustaffa (International Journal of Integrated Engineering, 2018)
Lowland tropical rainforests have the largest aboveground biomass compared to other types of tropical rainforest. Furthermore, lowland tropical rainforests have a high density of trees and various types of vegetation species. Due to the limitation in measurement method that occurs in lowland tropical rainforest, the information regarding aboveground biomass is very limited to small-scaled area compared with the existing method based on experimental plot tree census. Hence, this study suggested the upscaling method that enables the estimation of biomass for a larger area using a small size experimental plot. This study is conducted at Sungai Papan Royal Belum Forest Reserve, Perak with an area approximate to 22 hectares and based on the experimental plot of 100 × 100 m. Eight vegetation indices obtained from UAV multispectral images and field data are used to determine the best upscaling equation. This study successfully determined that TAGB VS SR gives the highest correlation with = 0.7224, RMSE= 1.1700 and t-test= 15.647/100. The final output of this research study shows the upscaling map of aboveground biomass concentration at Sungai Papan, Royal Belum Forest Reserve